Species and Density of Starfish (Asteroidea) in Seagrass Ecosystems at Pengudang Village, Bintan Regency, Kepulauan Riau - M. Adnin Firmansyah Simanjuntak; Adriman Adriman; Muhammad Fauzi (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Sea stars, members of the Echinodermata phylum, are closely associated with seagrass beds and play a role in the food chain. High seagrass cover supports a variety of biota, including sea stars. This study aims to determine the types and density of starfish (Asteroidea) in the seagrass ecosystem of Pengudang Village, Bintan Regency, Kepulauan Riau Province. This research was conducted in September 2024 in Pengudang Village, Bintan Regency, Kepulauan Riau Province. Starfish sampling and observation were conducted at three station points, with each station having three transect lines. Each transect contained ten observation plots measuring 1×1 m. Two species of starfish were found during the study in Pengudang village: Archaster typicus (73 individuals) and Protoreaster nodosus (14 individuals). The density of starfish found during research in Pengudang Village ranged from 700 to 13,700 individuals per hectare. Water quality conditions during the study were classified as good for supporting starfish life, with temperatures ranging from 29.7 to 31.3°C, current speeds from 0.055 to 0.076 m/s, salinity from 29.9 to 31.6 ppt, and dissolved oxygen from 6.82 to 7.66 mg/L.